65.9k views
0 votes
Solve for x.


1/2 ( 3/5x − 1/2) > x +3/8

User Kimstik
by
4.9k points

2 Answers

6 votes


(1)/(2) ((3)/(5) x-(1)/(2) ) > x+(3)/(8)

Simplify:


(3)/(10) x+-(1)/(4) > x+(3)/(8)

Subtract x from both sides:


(3)/(10) x+-(1)/(4) -x > x+(3)/(8) -x


-(7)/(10) x+-(1)/(4) > (3)/(8)

Add
(1)/(4) to both sides:


-(7)/(10) x+-(1)/(4) +(1)/(4) > (3)/(8) +(1)/(4)


-(7)/(10) x > (5)/(8)

Multiply both sides by
-(10)/(7):


(-(10)/(7) )*(-(7)/(10) x) > (-(10)/(7) )*((5)/(8) )

Since we are multiplying inequalities by negative numbers, the sign will reverse.


\fbox{x} < \fbox{-$(25)/(28) $}

User Dinesh Patra
by
5.2k points
0 votes

Answer:


x < - (25)/(28)

Explanation:

Given inequality:


(1)/(2)\left((3)/(5)x-(1)/(2)\right) > x+(3)/(8)

Distribute:


\implies (1)/(2)\cdot (3)/(5)x- (1)/(2)\cdot (1)/(2) > x+(3)/(8)


\implies (3)/(10)x- (1)/(4) > x+(3)/(8)

Add 1/4 to both sides:


\implies (3)/(10)x- (1)/(4) +(1)/(4) > x+(3)/(8)+(1)/(4)


\implies (3)/(10)x > x+(3)/(8)+(1)/(4)

Subtract x from both sides:


\implies (3)/(10)x-x > x+(3)/(8)+(1)/(4)-x


\implies (3)/(10)x-x > (3)/(8)+(1)/(4)

Rewrite fractions so that the denominators are the same on each side fo the inequality:


\implies (3)/(10)x-(10)/(10)x > (3)/(8)+(2)/(8)


\implies-(7)/(10)x > (5)/(8)

Multiply both sides by 10/7:


\implies-(7)/(10)x \cdot (10)/(7) > (5)/(8)\cdot (10)/(7)


\implies-x > (50)/(56)


\implies-x > (25)/(28)

Divide both sides by -1 (remembering to reverse the inequality sign):


\implies x < - (25)/(28)

User Xavier Haniquaut
by
5.7k points